Assessment of the Five Cs of Credit in the Lending Requirements of the Nigerian Commercial Banks - Oseni, Ezekiel (International Journal of Economics and Financial Issues, 2023)
Credit evaluation and decision like any investment decision requires utmost due diligence from the decision makers to avoid high default rates. It is expected of the lender to apply caution all the way by eliminating all forms of asymmetry information that could lead to adverse selection and non-performing loans. To avoid adverse selection and high default rates that could jeopardize the lender’s going concern and profitability, caution is the silent C emedded in the five Cs of credit. The study administered a structured questionnaire to all the Nigerian banks that survived the 2005 recapitalization era and were still in operations at the time of this study. While the structured questions required the respondents to rank the five Cs of credit based on the importance their credit policy and practice attached to them, the hypothesis tested centred on the impacts of the Cs of credit on risk asset quality. The qualitative data were also analyzed using a module of the SPSS statistical software. The study observed that all the Cs of credit have a direct and significant correlation with the asset quality (non-performing loan ratio). The study recommended that Caution which it considered as a slient C of credit embedded in the five Cs and the only C provided by the lender should be the watchword throughout the credit risk management process. It imay be pertinent to also note that while the traditional five Cs (character, capacity, capital, collateral and conditions) are required from the borrower, the caution is required from the lender as a check on traditional five Cs.